Enlace visión medio viable para la difusión de contenidos informativos y culturales de la Parroquia San Juan, Cantón Puebloviejo - Gavilanez Sanchez, Sandra Samantha (2020)
In the present case of study, the purpose of this was to make a direct approach with the habitants of the Parish of San Juan, Canton Puebloviejo and with the directives of the Channel “Enlace Vision” (Social medio of communication with cantonal coverage) and to determinate if the channel is a viable medium for the diffusion of informative content and cultural relating to the location aforementioned. To understand some important parameters both of channel like the habitants in question, was given pass to the application of recollection data technique, in this case the interview and the survey; for this reason this investigation traveled through a mixed study (Qualitative and Quantitative). In this way it was measured the grade of viability of the channel “Enlace Visión” by transmitting or disseminating informative and cultural content of the Parish San Juan de Puebloviejo. The interviewers provided relevant information to conduct the research, for this reason, through this studio, it will be known the level of television consumption existing in this locality, the confidence transmitted by this media and the level of acceptance that it will have in the case of be able to transmit content of informative and cultural quality